161k views
3 votes
What is the solution to the following system?

3x + 3y + 3z = -12
5x + 2y + 2z = -17
2x-4y - z = -20

User Abel Jojo
by
5.5k points

1 Answer

0 votes
To solve the systems, you have to use one of the equations to remove one of the variables from the rest of the equations. In this example, I use the third equation to get rid of the z in the other 2 equations. Then you can just use elimination to find one of the variables, and substitute values in the equations to find the rest.
What is the solution to the following system? 3x + 3y + 3z = -12 5x + 2y + 2z = -17 2x-example-1
User Mcmwhfy
by
5.0k points